BSCCO superconductor micro/nanofibers produced by solution blow-spinning technique - Cena, C. R.; Torsoni, G. B.; Zadorosny, L. [UNESP]; Malmonge, L. F. [UNESP]; Carvalho, C. L. [UNESP]; Malmonge, J. A. [UNESP] (Elsevier, 2017)
This paper presents the synthesis and characterization of BSCCO superconducting fibers synthesized by heat-treating poly(vinyl pyrrolidone) (PVP)/BSCCO precursor microfibers produced by the solution blow-spinning technique. Different concentrations (v/v) of the BSCCO precursor were added to the PVP solution to evaluate the influence of solution viscosity on fiber morphology. The production of PVP/BSCCO microfibers and their morphology were strongly influenced by the volatility of the solvent and the concentration of the added BSCCO in the solution. After heat-treatment, fibrous structures were obtained for the BSCCO system. The structural properties of the samples were analyzed by scanning electron microscopy (SEM) and X-ray diffraction (XRD). The XRD pattern revealed the formation of Bi2Sr2Ca1Cu2Ox and Bi1,9Sr1,8CuO5,5 phases. Finally, electrical measurements (R×T) showed electrical resistance decay at the transition temperature (Tc) that was typical of that observed in superconductor materials.
Keywords: Bi-2212; Nanofibers; Solution blow-spinning; Superconductor